Проблемы и основные подходы к решению задачи медицинской диагностики - Мельник, Карина Владимировна; Ершова, Светлана Ивановна (Харківський національний університет Повітряних Сил ім. Івана Кожедуба, 2011)
Рассмотрены основные проблемы, возникающие при решении задачи медицинской диагностики. Предлагаются подходы формализации медицинских данных для задачи диагностирования. Приведена классификация методов обработки данных и их основные особенности при решении задачи медицинской диагностики.

Basic problems, arising up at the decision of task of medical diagnostics, are considered. Approaches of formalization of medical information are offered for the task of diagnosing. Classification of methods of processing of data and their basic features is resulted at the decision of task of medical diagnostics.
Problems and basic approaches to solving the problem of medical diagnosis
Keywords: медицинская диагностика; представление знаний; семантические сети; фреймы; онтологии; нейросетевые технологии; medical diagnostics; representation of knowledges; semantic networks; frames; ontology; connectionist technology